PEMBERDAYAAN MASYARAKAT PADA PAGUYUBAN UKM KERAJINAN BAMBU BRAJAN MELALUI PENERAPAN DIGITAL MARKETING DI DESA SENDANGAGUNG MINGGIR SLEMAN - Yuni Istanto; Gunawan Nusanto; Sri Dwi Ari Ambarwati (Dharma: Jurnal Pengabdian Masyarakat, 2021)
This community service is a downstreaming of the research results that have been carried out by servants in 2020 with the influence of innovation on social media adoption on the marketing performance of Sleman SMEs. This community service partner is the Brajan Sleman Bamboo Craft UKM Association. The results of research conducted by researchers in 2020 show that many SMEs in Sleman, especially the Bambu Brajan SMEs, have greatly prevented Covid-19 and sales have decreased drastically. The decline in sales of bamboo handicrafts has caused the people in the Brajan area to be threatened with poverty. Research findings that have been carried out by researchers, show that the ability to change the direction of digital marketing is an urgent matter that causes sales to decline. This community service program is intended to assist SMEs producing Bamboo handicrafts in Brajan to be able to rise again during the new normal covid-19 pandemic. Some of these community service programs are carried out to help improve the skills of SME human resources in dealing with digital marketing, through training programs on social media creation, website creation, and how to enter the market to increase demand for products produced by bamboo craftsmen and assistance in improving HR soft skills. This community service is important to do. Bamboo SMEs in Brajan are very vulnerable to the COVID-19 crisis so that they are empowered to be strong in facing crisis conditions through mastering internet and digital technology. Of the various problems faced by partners, this community service justifies the problem with partners, namely the ability to adopt technology by Brajan bamboo handicraft SMEs.